(untitled) (Research, Society and Development, 2021)
Objective: this study aims to present an experience report lived by a student of the undergraduate course in Social Work during supervised curricular internships. Methodology: this is an experience report, with a descriptive nature. Results: the activities developed occurred because of Supervised Internships I, II and III, in a hospital in the Metropolitan Region of the city of Recife, capital of the state of Pernambuco, in the Emergency Service sectors, in the Intensive Care Unit and in the Transfusion Agency. The internships were carried out under the supervision of professors from the teaching unit and social workers from the internship field between the years 2019 and 2020. Conclusion: in view of the activities developed, it was possible to understand and learn about professional practice, the role of the assistant as a member of the multidisciplinary team and on the importance of this professional’s performance during the period of pandemic caused by Covid-19.